An integrated source–exposure–transport framework for risk-oriented management of mining-impacted groundwater contamination - Chang Liu; Yimin Sang; Fan Feng; Tingyu Yang; Qingyue Wang; Yanwei Wang; Heming Wang; Fujun Ma; Qingbao Gu (Journal of Environmental Chemical Engineering, 2026)

Criticality and scale effects in China's power lithium-ion battery system - Yue Zhang; Yao Wang; Fengmei Ma; Asaf Tzachor; Heming Wang (Journal of Environmental Management, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Modulation of Atlantic multidecadal oscillation on the relationship between ENSO and late-winter Southern Indian Ocean Dipole - Meng Xu; Haiming Xu; Jing Ma; Jiechun Deng; Yu Yuan; Heming Bai (Climate Dynamics, 2026)

Impact of steam explosion on Sorghum starch digestibility and physicochemical properties - Xiaoli Ma; Heming Wang; Yuan Zhang; Peiyan Li; Danyang Li; Kun Yu (Food Research International, 2025)

Corrigendum to “Multi-omics techniques to compare the potential of raw and processed licorice as a food supplement for ameliorating chronic fatigue syndrome” [Food Bioscience, 56, December (2023), 103334] - Wenxin Xia; Heming Zhang; Mengxin Tao; Hao Zhou; Jiahua Ma; Tingting Li; Xiaofen Huang; Xueyan Fu (Food Bioscience, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Effect of static magnetic field-assisted repeated freezing and thawing on quality characteristics, microstructure, and myofibrillar protein properties of lamb meat - Jinxiao Liu; Wang Heming; Pengfei Du; Weiting Wang; Yaobo Liu; Guoyuan Xiong; Kun Yu; Yanli Ma (Innovative Food Science & Emerging Technologies, 2025)

A decade of ecological and environmental research on the belt and road initiative: Evolution and future directions - Yongyue Gong; Heming Wang; Asaf Tzachor; Tomer Fishman; Fengmei Ma; Lingli Hou; Yao Wang; Wenju Sun; Yihan Song; Kai Fang; Wei-Qiang Chen; Yuri Mazei; et al. (Resources, Conservation and Recycling, 2025)

The evolution of research at the intersection of industrial ecology and artificial intelligence - Yongyue Gong; Fengmei Ma; Heming Wang; Asaf Tzachor; Wenju Sun; Junming Zhu; Gang Liu; Heinz Schandl (Journal of Industrial Ecology, 2025)
The intersection of artificial intelligence (AI) and industrial ecology (IE) is gaining significant attention due to AI's potential to enhance the sustainability of production and consumption systems. Understanding the current state of research in this field can highlight covered topics, identify trends, and reveal understudied topics warranting future research. However, few studies have systematically reviewed this intersection. In this study, we analyze 1068 publications within the IE–AI domain using trend factor analysis, word2vec modeling, and top2vec modeling. These methods uncover patterns of topic interconnections and evolutionary trends. Our results identify 71 trending terms within the selected publications, 69 of which, such as “deep learning,” have emerged in the past 8 years. The word2vec analysis shows that the application of various AI techniques is increasingly integrated into life cycle assessment and the circular economy. The top2vec analysis suggests that employing AI to predict and optimize indicators related to products, waste, processes, and their environmental impacts is an emerging trend. Lastly, we propose that fine‐tuning large language models to better understand and process data specific to IE, along with deploying real‐time data collection technologies such as sensors, computer vision, and robotics, could effectively address the challenges of data‐driven decision‐making in this domain.

Investigation of NO emission characteristics from co-combustion of methane and ammonia at high-altitude areas - Xiao Yang; Jianmin Gao; Biao Huang; Shijiu Ma; Min Xie; Qian Du; Yu Zhang; Heming Dong (Journal of Hazardous Materials, 2025)

Bridging environmentally extended input-output models and complex network analysis: A bibliometric analysis of trends and opportunities - Wenju Sun; Fengmei Ma; Asaf Tzachor; Yao Wang; Yongyue Gong; Chao Wang; Xiaoqian Hu; Heming Wang (Journal of Cleaner Production, 2025)

Multi-omics techniques to compare the potential of raw and processed licorice as food supplements for ameliorating chronic fatigue syndrome - Wenxin Xia; Heming Zhang; Mengxin Tao; Hao Zhou; Jiahua Ma; Tingting Li; Xiaofen Huang; Xueyan Fu (Food Bioscience, 2023)

Quantifying economic sectoral iron commodity use and related vulnerability in China's supply chains - Yao Wang; Fengmei Ma; Asaf Tzachor; Peng Wang; Heming Wang; Jie Lyu; Qiang Yue; Tao Du; Wei-Qiang Chen; Sai Liang (Resources, Conservation and Recycling, 2023)

Cascading impacts of global metal mining on climate change and human health caused by COVID-19 pandemic - Yao Wang; Heming Wang; Peng Wang; Xu Zhang; Zhihe Zhang; Qiumeng Zhong; Fengmei Ma; Qiang Yue; Wei-Qiang Chen; Tao Du; Sai Liang (Resources, Conservation and Recycling, 2023)

What Iodine Intervention Measures Should Be Taken in Different Water Iodine Areas? Evidence from a Cross-sectional Chinese Survey - Yang Du; Peng Liu; Fangang Meng; Lijun Fan; Qingzhen Jia; Weidong Li; Wen Jiang; Jing Ma; Heming Zheng; Peihua Wang; Dianjun Sun; Hongmei Shen (Biological Trace Element Research, 2022)

Liver sinusoidal endothelial cells are implicated in multiple fibrotic mechanisms - Heming Ma; Xu Liu; Mingyuan Zhang; Junqi Niu (Molecular Biology Reports, 2021)

Regional material flow accounts for China: Examining China's natural resource use at the provincial and national level - Heming Wang; Heinz Schandl; Guoqiang Wang; Lin Ma; Yao Wang (Journal of Industrial Ecology, 2019)
Over the last three decades, China has experienced the most dynamic economic development lifting living standards and resulting in fast‐growing use of natural resources. In the past, the focus has been on national MFA accounts which do not do justice to the second largest economy, home to 19% of the world population and having 30% of global material use. In this research, we calculate material extraction for China at the regional level during 1995–2015 using the most recent available statistical data and applying the most up‐to‐date international calculation methods. In particular, we combine a bottom‐up and top‐down approach for constructing the dataset of China's economically used Domestic Extraction (DEU) in an integrated way. This approach also improves the Chinese national material flow accounts and allows us to present a reliable database of DE of materials for China to date. Our new dataset provides the basis for calculating material footprints and environmental impacts of China's regions. The dataset enables us to evaluate regional resource efficiency trends in China. We find that during the past two decades, China's material use has grown strongly from 11.7 billion tonnes in 1995 to 35.4 billion tonnes in 2015. Material use has accelerated between 2000 and 2010 but slowed down between 2010 and 2015 reflecting the economic contraction caused by the Global Financial Crisis which reduced the global demand for China's manufacturing and a reorientation of China's economic policy settings toward quality of growth. Unsurprisingly, different regions play different roles in the supply chain of materials, achieving different economic performances resulting in very diverse material efficiency outcomes. This information is important to allow for a targeted policy approach to increase resource efficiency, reduce environmental impacts of resource use, and grow wellbeing in China with large positive implications for global sustainability. This study provides the basis for the development of relevant resource management policies for different regions in the future.

Fabrication of Carvedilol Nanosuspensions Through the Anti-Solvent Precipitation–Ultrasonication Method for the Improvement of Dissolution Rate and Oral Bioavailability - Dandan Liu; Heming Xu; Baocheng Tian; Kun Yuan; Hao Pan; Shilin Ma; Xinggang Yang; Weisan Pan (AAPS PharmSciTech, 2012)